The Impact of Electronic Word Of Mouth (EWOM), Influencers Marketing, and Brand Image on Purchase Intention via Online Travel Agents (OTA) - Dewi Purnama; Natasya Dewi Rahayu; Achmad Muhyidin Arifa'i; Nashrullah Nashrullah (Green Publisher, 2025)
This study aims to examine and analyze the variables of Electronic Word of Mouth (X1) and Influencers Marketing (X2) on Purchase Intention through Online Travel Agent (Z) with the Brand Image (Y) variable as mediation on Tiket.com platform. This study uses a quantitative method with random sampling techniques. The respondents in this study consisted of 296 people and then the results were processed using IBM SPSS Statistics 25. Data collection was carried out by survey method using a questionnaire through Google Form as a research instrument. After conducting a hypothesis test, the results show that Electronic Word of Mouth, Influencers Marketing and Brand Image have a positive significant influence on Purchase Intention on the Tiket.com application.